Thermal performance of hybrid magnetized nanofluids flow subject to joint impact of ferro oxides/CNT nanomaterials with radiative and porous factors. (January 2023) - Qureshi, M Zubair Akbar; Raza, Qadeer; Eldin, Sayed M.; Zafar, Maria; Ali, Bagh; Siddique, Imran
Abstract: We discussed the thermal performance of hybrid nanofluid flow in the presence of ferroxidase and carbon nanotube nanoparticles. Furthermore, under the impact of magnetohydrodynamics and the Reynolds number, which is related to expansion and contraction phenomena. We simultaneously examine the effects of heat radiation and porosity. The suitable similarity transformation is applied and then the mathematical problem has been solved by employing the numerical shooting method. Plots of the skin friction coefficient, temperature, and Nusselt number on various non-dimensionless parameters are shown via the bottom and upper porous walls. The thickness of the nano-layer, the ionic radii, and the shape of the hybrid nanoparticles with volume fraction, have fruitful results related to industrial sciences. Hybrid nano-fluids, as opposed to conventional nano-fluids, are a good means of heat transmission. Hybrid nanoparticles contain 2 → 4% volume fractions having a significant effect on skin friction. Overall, the magnitude values of Reynolds number 1 → 4, enhance the Nusselt number. Thermal radiation in the presence of nanoparticles with hybrid nanomaterials volume fraction 1% has a fruitful impact on heat transfer rate.